Selling / Building Partnerships - Castleberry Stephen B; Tanner John; Weitz Barton A (Mcgraw Hill Irwin, 2001)
Prologue, The Field of Selling, Selling and Salespeople, Building Partnering Relationships, Ethical and Legal Issues in Selling, Knowledge and Skill Requirements, Buying Behavior and the Buying Process, Using Communication Principles to Build Relationships, Adaptive Selling for Relationship Building, The Partnership Process, Prospecting, Planning the Sales Call, Making the Sales Call, Strengthening the Presentation, Responding to Objections, Obtaining Commitment, Building Long-Term Partnerships, Special Applications, Format Negotiating, Selling to Resellers, The Salesperson as Manager, Managing Your Time and Territory, Managing within Your Company, Managing Your Career, Notes, Glossary, Indexes.
Prologue, The Field of Selling, Selling and Salespeople, Building Partnering Relationships, Ethical and Legal Issues in Selling, Knowledge and Skill Requirements, Buying Behavior and the Buying Process, Using Communication Principles to Build Relationships, Adaptive Selling for Relationship Building, The Partnership Process, Prospecting, Planning the Sales Call, Making the Sales Call, Strengthening the Presentation, Responding to Objections, Obtaining Commitment, Building Long-Term Partnerships, Special Applications, Format Negotiating, Selling to Resellers, The Salesperson as Manager, Managing Your Time and Territory, Managing within Your Company, Managing Your Career, Notes, Glossary, Indexes.